The Parisian worlds of Frédéric Chopin - Atwood, William G., 1932-2011 (Yale University Press, 1999)
Fleeing his native Warsaw, Chopin stopped in Paris in 1831 and stayed there until his death. The author "re-creates the Paris that Chopin knew, providing vivid details about its places, people, and politics, and showing how these affected [Chopin].--Jacket